2014
DOI: 10.1177/070674371405900308
|View full text |Cite
|
Sign up to set email alerts
|

A Narrative Review of Recent Developments in Knowledge Translation and Implications for Mental Health Care Providers

Abstract: Despite limitations in existing evidence, the concept and practice of KT holds potential value for mental health care providers. Understanding of, and familiarity with, effective approaches to KT holds the potential to enhance providers' treatment approaches and to promote the use of new knowledge in practice to enhance outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 65 publications
(130 reference statements)
3
17
0
Order By: Relevance
“…The blogs were also written in a clear and concise manner, with minimal jargon, and a conversational tone [14, 25], akin to the style of newspaper reports [26]. They were also delivered directly to users’ inbox via a weekly newsletter [27], and presented in a format suitable for mobile phones, tablets or related devices [26, 28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blogs were also written in a clear and concise manner, with minimal jargon, and a conversational tone [14, 25], akin to the style of newspaper reports [26]. They were also delivered directly to users’ inbox via a weekly newsletter [27], and presented in a format suitable for mobile phones, tablets or related devices [26, 28].…”
Section: Introductionmentioning
confidence: 99%
“…They were also delivered directly to users’ inbox via a weekly newsletter [27], and presented in a format suitable for mobile phones, tablets or related devices [26, 28]. The blogs often summarised relevant research findings [25, 29] and provided clear and concrete recommendations [14, 30].…”
Section: Introductionmentioning
confidence: 99%
“…As background to this larger study, a narrative review conducted by one of the authors identified substantial gaps between science and practice in the field of mental health. The review found that KT strategies may hold particular value in strengthening MHS (Goldner ). It concluded that
More so than in other areas of health care, mental health is an area in which detrimental and stigmatizing misinformation is widespread and resistant to modification, both among the general public and health care providers … Consequently, effective approaches to KT may be particularly important to facilitate exchange and uptake of high quality knowledge related to mental health.
…”
Section: Introductionmentioning
confidence: 99%
“…It concluded that
More so than in other areas of health care, mental health is an area in which detrimental and stigmatizing misinformation is widespread and resistant to modification, both among the general public and health care providers … Consequently, effective approaches to KT may be particularly important to facilitate exchange and uptake of high quality knowledge related to mental health. (Goldner )
…”
Section: Introductionmentioning
confidence: 99%
“…This experience immersed me in the fledgling fields of knowledge translation and implementation science. 27 Despite significant advances in health care practice and policy, efforts to apply such advances to improve the quality of services often falter and perish during the stage of implementation. 28 Health care services reside in complex systems and, once set along a path, they may be difficult to shift, even when a change in course may be of great benefit to all parties.…”
mentioning
confidence: 99%